Difficulties in the Accounting Research–Practice–Teaching Relationship: Evidence from Romania - Corina Grosu; Alina Carmen Almasan; Cristina Circa (Journal of Accounting and Management Information Systems (JAMIS), 2015)
For more than 40 years, there has been a continuous and heated debate in literature, with regard to the difficult relationship between the three components of the accounting profession: research, practice and teaching. With few exceptions, there is a large consensus of opinions that there is at least a gap between accounting research and practice, if not a schism. In bridging the gap, a better communication between the two parties seems to be the best solution and the professional bodies, the most proper moderator. Under these circumstances, starting from the identified results of previous research, we investigated the mutual relationships within the research-practice-teaching triangle, aiming at identifying and assessing the obstacles that determine and maintain the gap between the accounting academia and practice in the Western part of Romania. With regard to the research-practice line, our results were not significantly different from the ones of other authors. We found that the accounting profession in Romania is characterized by a disruption between the interests of academics and practitioners, determined by a lack of communication between the two parties. Our personal contribution to the debate consists however in a thorough analysis of the role of university education in narrowing the existing gap between academia and practice.
Keywords: M41; 650; accounting academia; practice; research; teaching; education